STUDENTS’ PERCEPTIONS ON USING TIKTOK DUET IN MINIMIZING EFL ANXIETY AND ENHANCING SPEAKING SKILLS - Annisa Nadya Fauziah; Pasca Kalisa (ENGLISH, 2025)
This research explored EFL students’ perceptions of using TikTok Duet to practice speaking and minimize their speaking anxiety, and their challenges and benefits from using that feature. This current research employed a descriptive qualitative method, involving 49 students who completed the questionnaire and 6 students who participated in a semi-structured interview. The findings revealed that TikTok Duet had a good influence on students’ achievement in learning because TikTok provided a convenient and enjoyable environment. Students reported that their anxiety decreased while using TikTok Duet, and they found it helpful in improving their speaking development, such as pronunciation, fluency, and vocabulary. This study also found several challenges students face, such as distractions from unrelated content, fast-running video texts, and difficulties finding suitable learning content. In conclusion, TikTok Duet can be a very beneficial digital tool for supporting EFL students in reducing anxiety and developing speaking skills when they use it appropriately.